Original method of the frontal abdominal wall defect reconstruction using the principle of the reconstructive-restorative surgery - I. P. Khomenko; E. V. Tsema; V. Yu. Shapovalov; S. V. Tertyshny; P. P. Yermuraki (Kazimierz Wielki University, 2021)
The author srepresent the original clinical data devoting to the further progress in reconstructive surgery. The methodology of the staged anterior abdominal wall defect reconstruction using the Keystone method was used firstly. The aim of the work is to demonstrate the peculiarity of preoperative preparation of patients with the anterior abdominal wall wounds complicated by small intestinal fistulas. The article uses the clinical materials of the concrete patient treatment in the Department of surgical infection of the South Region Military Medical Clinical Centre (Odessa, Ukraine) using the principle of the reconstructive-restorative surgery. The clinical case of the successful surgical treatment of anterior abdominal wall eventration, resulting from numerous laparotomies with pronounced lateralization of the wound, has shown that the solution to this problem should be based on the principles of reconstructive surgery. Preoperative modelling of full-layer flaps using a combined technique (infrared camera FLIR and portable Doppler SONO Trax) reduces the risk of necrosis of the movable flap and accelerates the process of closing of the defect of the anterior abdominal wall. Staged ("step-by-step") surgical treatment of the postoperative wound of the anterior abdominal wall by reconstruction via to the Keystone method showed a positive and rapid result of solving such a difficult problem as eventration complicated by small intestinal fistula. Restoration of the integrity of the anterior abdominal wall should be considered from the standpoint of reconstructive-restorative features